Carbon nanoflake-nanoparticle interface: A comparative study on structure and photoluminescent properties of carbon nanoflakes synthesized on nanostructured gold and carbon by hot filament CVD. (November 2017) - Wang, B.B.; Qu, X.L.; Zhu, M.K.; Levchenko, I.; Keidar, M.; Zhong, X.X.; Xu, S.; Ostrikov, K.
Abstract: Three dimensional vertically-oriented carbon nanoflakes grown on carbon and gold nanoparticles by the hot filament chemical vapor deposition in CH4 environment demonstrate quite similar structure and composition, but drastically different room temperature photoluminescent properties. The interfacial interactions were asserted to be the main reason for the differences in the optical emission. The mechanisms of highly oriented growth, generation and enhancement of photoluminescence were investigated, and it was demonstrated that the formation of oriented nanoflakes resulted from the stress produced in the carbon layers on carbon and gold nanoparticles. Specifically, deformation of nanoparticles and difference in the expansion rates of carbon layer, gold and carbon nanoparticles are the main causes for the stress formation. The oriented growth of carbon nanoflakes is maintained by the repulsion effect between the carbon nanoflakes due to the net charge produced from the hydrocarbon radicals on the edges of carbon nanoflakes via charge transfer between H and C atoms. The photoluminescence generation of carbon nanoflakes is related to the sp 2 carbon clusters on the edges of carbon nanoflakes. Stronger green photoluminescent emission from the carbon nanoflake/gold nanoparticle system than from the carbon nanoflake/carbon nanoparticle system is the result of the intense plasmon emission from gold nanoparticles. Graphical abstract: